Human capital issues in Malaysian MICE industry from the expert’s perspective / Nadia Mohd Adros and Hassnah Wee - Mohd Adros, Nadia; Wee, Hassnah (UiTM Press, Universiti Teknologi MARA Selangor, 2019)
Meeting, Incentive, Convention, and Exhibition (MICE) industry faced quite intense challenges due to its growth and demand in the industry. Besides, the industry encounters a problem related to human capital, such as insufficient talents, which gives a negative impact on the industry. The objective of this study is to explore and understand human capital issues in the MICE industry. This research was conducted using the qualitative method to explore the related issues in the Malaysian MICE industry. The data obtained from the interview session and document analysis. Respondents were identified using the purposive sample and snowball techniques among meetings and exhibition management experts in the industry. Thematic analysis was employed to find the themes for this study. Several issues identified which are lack of industry awareness, insufficient skilled staff, generation Y, alignment of the industry with the university, internship and lack of networking among stakeholders. The findings are useful for the stakeholders of the MICE industry to recognise the talents and retaining the workforce in the industry.